KAJIAN FAKTOR PENENTU KINERJA USAHA KECIL DI KOTA MAKASSAR - Awaluddin, Murtiadi (Jurnal Minds: Manajemen Ide dan Inspirasi, 2015)
This research aims to know and analyze influence of entrepreneurial personality, information access and innovation on the small business Performance in the city of Makassar. This research uses a explanatory research method, and the population is entire small businesses registered in the Department of Cooperatives and SMEs Makassar. The small business criteria based on criteria according to Act No. 20 of 2008 about the micro, small and medium enterprises (SMEs). Samples in drag with simple random sampling method and maximum Likehood method of estimation (ML) by the number of respondents who shared 100. Data analysis was done using structural equation model Structural Equation Modeling or (SEM) Results of the analysis show that the entrepreneurial personality, information access and innovation influential positive and significant to small business Performance in the city of Makassar